The Role of the Interprovincial Transfers in the ß-Convergence Process. Further Empirical Evidence for Canada - Rodriguez, Gabriel (Université d'Ottawa | University of Ottawa, 2003)
Based on the approach of Timljonavich and Vogelsang (2002), I present empirical evidence of the role of the federal transfers on the B-convergence process in Canadian provinces. Using information on personal income for the period 1926-1999, the principal conclusion is that the interprovincial transfers were not determinant or decisive to the attainment of deterministic convergence in the Canadian provinces. Their role have been to accelerate the convergence process, particularly in poorer provinces. / Fondée sur l’approche de Timljonavich and Vogelsang (2002), je présente l’évidence empirique du rôle des transferts fédéraux dans le processus entraînant la convergence B pour les provinces canadiennes. Utilisant l’information sur le revenu personnel pour la période de 1926 à 1999, la principale conclusion qui en ressort est que les transferts inter-provinciaux ne se sont pas avérés déterminants ou décisifs dans l’atteinte d’une convergence déterministique pour les provinces canadiennes. Leur rôle a plutôt été d’accélérer le processus de convergence, en particulier pour les provinces moins nanties.
Keywords: ß-Convergence; Regional per capita Income; Trend Functions; Serial Correlation; I(0) and I(1) Process; Convergence ß; revenu régional par habitant; tendance; corrélation sériale; processus I(0) et I(1)